PEMBERDAYAAN MASYARAKAT SEBAGAI UPAYA PROMOTIF DAN PREVENTIF SINDROM METABOLIK PADA MASYARAKAT MELALUI PROGRAM MINCEU ANTI- MEARO - Yuniarty, Tuty; Atmaja, Ratih Feraritra Danu; Orno, Theosobia Grace; Sari, Julianti Isma; Fauzi, Ahmad Zil; Putra, Ahmat Rediansya (Jurnal Abdi Insani, 2025)
nfectious diseases remain a major public health concern due to their highmorbidity and mortality rates, including conditions such as cardiovasculardiseases, cancer, chronic respiratory diseases, and diabetes mellitus.Cardiovascular disease and diabetes are strongly associated with centralobesity, dyslipidemia, elevated fasting blood glucose, and hypertension.Metabolic syndrome is defined as a constellation of complex metabolicabnormalities that significantly increases the risk of developing cardiovasculardisease and type II diabetes mellitus. The key components implicated in thepathogenesis of metabolic syndrome include hypertension, central obesity,insulin resistance, and atherogenic dyslipidemia. This study aimed to educatethe community about metabolic syndrome while simultaneously conductingearly detection. The screening procedures included measurements of bloodpressure, waist circumference, blood glucose levels, the measurement of totalcholesterol, triglycerides, and low density lipoprotein (LDL) levels wasperformed using the Point of Care Testing (POCT) method. A total of 52respondents participated in this activity, consisting of 57.7% (n=30) females and42.3% (n=22) males. The results indicated that 92.3% (n=48) had normal bloodglucose levels, 100% (n=52) had normal total cholesterol, and 21.2% (n=11) hadnormal LDL levels. Normal blood pressure was observed in 34.6% (n=18), while67.3% (n=35) were found to have central obesity. Overall, 9.6% (n=5) ofrespondents were diagnosed with metabolic syndrome, whereas 90.4% (n=47)were not. Most respondents demonstrated metabolic risk factors such ashypertension, central obesity, and elevated LDL levels, despite having normalblood glucose and total cholesterol. These findings underscore the importanceof continuous public health education and targeted interventions to preventand reduce the prevalence of metabolic syndrome in the community.